PEMENUHAN HAK NAFKAH PEREMPUAN PASCA CERAI GUGAT - Montolalu, David; Djafar, Marwan; Insani, Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Divorce lawsuit is the termination of a marriage bond which is the result of a petition by the wife to the Religious Court, where the husband gives his consent, so that his petition is granted by the Religious Court. This study aims to determine how to fulfill women's living rights after a divorce lawsuit. This study uses an empirical research method (field research) or field research, namely research whose objects are regarding symptoms, events, and phenomena that occur in society, institutions or the State which are non-library by looking at. With Research Results The results of the study show that the fulfillment of women's rights in SEMA No. 3 of 2018 has not been effective until now. This is because social and cultural factors have not been running well. It can be seen from the conditions of the people of Gorontalo City, the majority of whom are not aware or understand the rules for fulfilling women's rights after a divorce lawsuit in SEMA No. 3 of 2018, besides that the people of Gorontalo City have not obeyed and implemented these rules. This happens because the lack of sensitivity to education also affects the mindset of the community who do not consider carefully before deciding to file for divorce in Court